The real-world effectiveness of defocus incorporated multiple segments and highly aspherical lenslets on myopia control: a longitudinal study from the French myopia cohort - Jost B Jonas; Serge Resnikoff; Rupert Bourne; Alain M Bron; Nicolas Leveziel; Rime Najji; Mark Bullimore; Mathieu Naudin; Clément Giraud (BMJ Open Ophthalmology)
Aims To evaluate the efficacy of myopia control by spectacle lenses in a real-world study.Methods This is a longitudinal, retrospective, comparative, observational, real-world study of the French Myopia Cohort. Records of prescriptions for optical correction, gender and age were collected from 1500 opticians between 2020 and 2023. The study cohort consisted of myopic children aged 4 to 15 years who were assigned to three groups: two control groups wearing single vision lenses (SVL) and one intervention group wearing myopia control spectacles (MCS); either defocus incorporated multiple segments (DIMS, n=1786) or highly aspheric lenses (HAL, n=585). The first SVL group was matched to the MCS group for age, sex and initial refractive error (first matching), and the second SVL group was matched for the same criteria and myopia progression during the first 6 months of follow-up (second matching).The difference in myopia progression was calculated between SVL groups and the MCS group. DIMS and HAL were also compared for myopia progression.Results A total of 2542 children (mean age of 9.5 years and mean spherical equivalent of −2.3 D at baseline) were included in each of the three groups. The mean progression rates for MCS were by +0.59 D (95% CI +0.57 to +0.62D; p<0.001) after the first matching and by +0.30 D (95% CI +0.28 to +0.32D; p<0.001) after the second matching, in comparison to the SVL groups. Children wearing HAL spectacles showed slightly less myopia progression (difference in progression = +0.14 D, 95% CI = +0.10 to +0.18, p<0.001) compared with the DIMS group.Conclusions Although there are some limitations, including its retrospective design, the lack of lifestyle and environmental data and the use of SE rather than axial length, this study showed that in a real-world setting, both DIMS and HAL spectacles demonstrated efficacy in reducing myopia progression. While a statistically significant lower myopia progression rate was observed in the HAL group, this difference was not clinically meaningful. This study also showed that DIMS and HAL reduce myopia progression among younger children aged 4 to 6 years.